2005
DOI: 10.1007/s10551-005-2926-x
|View full text |Cite
|
Sign up to set email alerts
|

Management Educators’ Expectations for Professional Ethics Development

Abstract: Professional associations, like the Academy of Management, exist to foster and promote scholarship, exchange among faculty, and an environment conducive to member professional ethics development. However, this last purpose of such organizations has received the least amount of attention. Moreover, previous research has demonstrated that there are differences in perceived needs for professional ethics development between tenured and untenured faculty. In the current research 260 Academy of Management members we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…To be sure, there is evidence of training in business ethics (Gandz and Hayes, 1988;Maclagan, 2002;Payne, 1988;Petrick and Scherer, 2005;Rossouw and van Vuuren, 2003;Warren and Tweedale, 2002); however, training based on the organization's view of 'ethics' may be insufficient. The critical factor, therefore, is not so much ethics as narrowly determined by the organization in terms of its own business interests, but that organizations need to be aware of ethical tensions placed on individuals, whether stemming from their professional obligations, or their personal ethical standards.…”
Section: Discussionmentioning
confidence: 99%
“…To be sure, there is evidence of training in business ethics (Gandz and Hayes, 1988;Maclagan, 2002;Payne, 1988;Petrick and Scherer, 2005;Rossouw and van Vuuren, 2003;Warren and Tweedale, 2002); however, training based on the organization's view of 'ethics' may be insufficient. The critical factor, therefore, is not so much ethics as narrowly determined by the organization in terms of its own business interests, but that organizations need to be aware of ethical tensions placed on individuals, whether stemming from their professional obligations, or their personal ethical standards.…”
Section: Discussionmentioning
confidence: 99%
“…The task force proposed a code of ethical conduct, the Academy of Management Code of Ethical Conduct (AMCEC) that was eventually approved in 1990 by the organization's governing board and voting membership of the Academy (Petrick and Scherer 2005). A copy of the initial version of the AMCEC can be found in a 1991 issue of Academy of Management Journal (Anonymous 1991).…”
Section: The Academy Of Management Code Of Ethicsmentioning
confidence: 99%
“…Due to disagreements among Academy board members concerning early recommendations related to certain educational and implementation/enforcement practices, the focus during the first 15 years after the code's passing was only on the educational and research dimensions of the AMCEC (Petrick and Scherer 2005).…”
Section: The Academy Of Management Code Of Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these variables are likely to have similar effects on the marketing educators' perceptions of acceptability of questionable behavior. Based on past research, several factors related to the educational and institutional environment were found to account for differences in ethical judgment between tenured and nontenured marketing educators (Petrick and Scherer, 2005). When compared to tenured faculty, non-tenured faculty experience less job security, potential for denial of tenure, and perceptions of mistreatment by their administrators and tenured colleagues.…”
Section: Tenure Rank and Phd Possessionmentioning
confidence: 99%